Determinants of Informal Sector Employment in Urban Labor Markets in Cameroon - YAH, NEBA Cletus; TINGUM, NGEH Ernest; KUM, FUEIN Vera (Jurnal Ekonomi dan Studi Pembangunan, 2018)
This study uses data from the Cameroon Survey on Employment and the Informal Sector (CSEIS) carried out in 2010 by the National Institute of Statistics (NIS) to examine the determinants of informal sector employment in the urban areas of Cameroon. The study applies a multinomial logit model to analyze gender and age group differences. The study finds that the determinants of informal employment in Cameroon`s urban labor market vary with gender and age group.Keywords:Â Informal Sector, Employment, Urban Labor MarketsJEL Classification: J23, J24